2015
DOI: 10.4067/s0717-65382015000100004
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización trófica de Orestias (Teleostei: Cyprinodontidae) en el Parque Nacional Lauca

Abstract: RESUMENLos peces muestran una amplia diversidad de comportamientos alimentarios, algunas veces asociados con morfologías específi cas, las cuales pueden refl ejar adaptaciones para usar los recursos dependiendo de su hábitat. En los sistemas acuáticos aislados, los peces son un buen modelo de estudio para entender las relaciones trófi cas. Este estudió evaluó la dieta de cinco especies de Orestias, las cuales habitan ocho sitios diferentes en la Región de Arica y Parinacota, Parque Nacional Lauca. Se analizaro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The short time since the events that originated this process has not allowed a complete lineage sorting among these populations in spite of the morphological differences that have been described and that motivated the description of different nominal species. In spite of the genetic and phylogeographic differentiation detected in this study, up to now there is no evidence of reproductive isolation among the groups and they do not appear to have developed ecological specialization, at least not at the trophic level [ 43 ]. There are also indications that individuals of these groups could maintain contact in the Parinacota wetland by sporadic migrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The short time since the events that originated this process has not allowed a complete lineage sorting among these populations in spite of the morphological differences that have been described and that motivated the description of different nominal species. In spite of the genetic and phylogeographic differentiation detected in this study, up to now there is no evidence of reproductive isolation among the groups and they do not appear to have developed ecological specialization, at least not at the trophic level [ 43 ]. There are also indications that individuals of these groups could maintain contact in the Parinacota wetland by sporadic migrations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent trophic studies of Orestias in the LNP watersheds showed low prey richness and dietary range, which was related to the reduced size and shallow depth of these systems, with mostly microinvertebrates inhabiting the macrophyte belt. Thus, the local populations of Orestias showed similar dietary habits associated with prey availability [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lower values than 0.60 are considered as a specialized diet using a low resource number, and values above 0.60 as a generalist (Krebs, 1999). Pianka’s symmetric index (1974) was measured to estimate the niche overlap in the diet composition between each species, depth and season (Guerrero et al , 2015). It is considered a biologically significant overlap when the value of this index exceeds 0.6 (Pianka, 1974).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the results of diet of five species of Orestias which inhabit eight different sites of the Arica and Parinacota Region, Lauca National Park, Chile. Show a pooled diet [39].…”
Section: Discussionmentioning
confidence: 99%